2008
DOI: 10.1177/216507990805601004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perceptions, and Attitudes of Managers, Coworkers, and Employed Breastfeeding Mothers

Abstract: Employer attitudes and practices toward breastfeeding mothers are discouraging overall. Mothers who believe that breastfeeding whileemployed cannot be done withouta considerable amount of additional work and stress may not even consider breastfeeding. Although it is known that lower income women tend not to breastfeed while employed, the relationship between type of employment and sustaining breastfeeding has not been clearly explained. Manywomen identifyemployment as a barrier to breastfeeding. Some elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This result is in agreement with other research showing reported attitudes often are not reflected in employer policies and practices. 26 As illustrated in the highlighted themes, this study's informants commonly reported demand as an influential factor in the degree of WBS they would provide. All informants shared the belief that there was little demand for WBS regardless of the size of their business.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This result is in agreement with other research showing reported attitudes often are not reflected in employer policies and practices. 26 As illustrated in the highlighted themes, this study's informants commonly reported demand as an influential factor in the degree of WBS they would provide. All informants shared the belief that there was little demand for WBS regardless of the size of their business.…”
Section: Discussionmentioning
confidence: 96%
“…18,19,22,23 On the business side, employers hold a range of attitudes about breastfeeding employees, offer varying degrees of support for breastfeeding in the workplace, and express concerns about the difficulties of providing formal breastfeeding support, including monetary constraints, challenges of providing breaks, and limited space. 19,[24][25][26][27] Even when generally positive, employer attitudes about breastfeeding have not translated into practices supporting breastfeeding mothers in the workplace. 20 This paradox can be analyzed within the framework of Fishbein and Ajzen's Theory of Reasoned Action (TRA).…”
Section: Clinical Research Reportmentioning
confidence: 99%
“…Previous research has also suggested the importance of interpersonal communication in addition to policies but has provided few specific solutions. 7-10,12,14,18-20,25,26 The participants in this study suggested that mothers bring this issue to the attention of employers. However, as this study and others suggest, employees may not feel comfortable broaching the issue, which may keep employers unaware of employees’ needs.…”
Section: Discussionmentioning
confidence: 76%
“…One potential barrier to continued breastfeeding can be challenges encountered when mothers return to work. 6-12,18-20 Therefore, the objective of this project is to describe interpersonal communication about workplace breastfeeding support.…”
Section: Introductionmentioning
confidence: 99%
“…Women who spend most of the day at workplaces need support of their colleagues during breastfeeding. [32] Dabritz et al reported that having colleagues who support breastfeeding in workplaces contributed positively to longer maternal breastfeeding periods. [33] In our study, it was determined that some of the women interviewed did not receive support from their colleagues while using legal breastfeeding breaks.…”
Section: Discussionmentioning
confidence: 99%